Development of an integrated cardiac rehabilitation program to improve the adaptation level of patients after acute myocardial infarction - Wang, Xiyi; Xu, Li; Lee, Geraldine; Song, Antai; Shao, Jing; Chen, Dandan; Zhang, Hui; Chen, Hanfen (Frontiers in Public Health, 2023)
Background Individual’s adaptation following acute myocardial infarction (AMI) and low attendance of whole-course cardiac rehabilitation (CR) are significant issues. For optimal health post AMI, an integrated CR program aiming at individual’s adaptive behaviors is imperative for improving the CR efficiency and patients’ outcomes. This study aims to develop theory-guided interventions to increase CR attendance and adaptation level of patients post-AMI. Methods This study was conducted in a tertiary hospital from July 2021 to September 2022 in Shanghai China. Guided by the theory of adaptation to chronic illness (ACI theory), the study followed the Intervention mapping (IM) framework to develop the interventions for CR program. Four phases included: (1) needs assessment of patients and facilitators using a cross-sectional study and semi-structured, in-depth interviews, (2) identification of implementation outcomes and performance objectives, (3) selection of theoretical methods to explain the mechanism of patients’ adaptive behaviors and to use for behavior change, and (4) development of implementation protocol from the results of the previous phases. Results A total of 226 AMI patient-caregivers paired samples were eligible for the data analysis, 30 AMI patients participated in the qualitative inquiry, 16 experts in the CR field evaluated the implementation protocol, and 8 AMI patients commented on the practical interventions. Following the IM framework, an integrated cardiac rehabilitation program using mHealth strategies was developed for AMI patients to facilitate CR attendance and completion, to improve their adaptation level and health outcomes. Conclusion Using the IM framework and ACI theory, an integrated CR program was developed to help guide the behavior change and improve adaptation among AMI patients. The preliminary findings suggest that further intervention in enhancing the combination of three-stage CR is required. A feasibility study will be conducted to assess the acceptability and effectiveness of this generated CR intervention.